2018
DOI: 10.32404/rean.v5i2.1872
|View full text |Cite
|
Sign up to set email alerts
|

Manejo Da Mucuna-Preta Na Supressão De Plantas Daninhas Na Cultura Da Alface-Crespa

Abstract: Plantas de cobertura podem causar a supressão de plantas daninhas devido aos efeitos físicos e alelopáticos produzidos pela palhada. O objetivo deste trabalho foi o de avaliar o manejo da palhada de mucuna-preta (superficial ou incorporada) no controle de plantas daninhas na cultura da alface-crespa. O delineamento experimental foi o de blocos ao acaso, dispostos em parcelas subdividas, com quatro repetições. As parcelas compreenderam os dois sistemas de manejo de palhada da mucuna-preta (superficial ou incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Using different types of cover crops, Resende et al (2005) and Santos et al (2011) also reported an increased carrot crop yield of, in average, 32 and 13%, respectively. In other crops, such as lettuce (Lactuca sativa L.) and strawberry [Fragaria × ananassa (Weston) Duchesne ex Rozier], the use of soil cover provided gains of 32 and 2.5% in commercial yield, respectively (Barbosa et al, 2018;Tonin et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Using different types of cover crops, Resende et al (2005) and Santos et al (2011) also reported an increased carrot crop yield of, in average, 32 and 13%, respectively. In other crops, such as lettuce (Lactuca sativa L.) and strawberry [Fragaria × ananassa (Weston) Duchesne ex Rozier], the use of soil cover provided gains of 32 and 2.5% in commercial yield, respectively (Barbosa et al, 2018;Tonin et al, 2017).…”
Section: Resultsmentioning
confidence: 99%